Influence of aspect on vegetation dynamics: insights into the understory vegetation diversity of the dry temperate forests of South Waziristan Agency, Pakistan - Khan, Imran; Zahid, Din Muhammad; Zubair, Muhammad; Manzoor, Syed Amir; Yasin, Ghulam; Mohammad, Mamoona Wali; Khan, Khalid Ali; Rahman, Shafeeq Ur; Qin, Anzhen (Frontiers in Forests and Global Change, 2023)
The dry temperate forests of Pakistan exhibit rich diversity of understory floral species. These important and endemic plant species play a pivotal role in ecosystem functioning and providing livelihoods to the forest communities. South Waziristan, located in the southwest of Pakistan, is known for its rare pure stands of Pinus gerardiana Wallichex. D. Don forests. The rapidly expanding population and current state of affairs are leading to deforestation and causing disturbance to the understory vegetation of this valuable forest. The current study aims to fill the currently scanty information present in the literature regarding the diversity status of understory vegetation in P. gerardiana forests. Data of understory vegetation diversity were gathered for the northern and southern aspects of the forest. A 50 m2 sampling plot along with the placement of fifty 1x1m2 quadrats on both sites were laid out to determine species dominance, diversity, and evenness using Simpson, Shanon, Marglef, and Buzas–Gibson indices. The study depicted 612 individuals of about 29 species representing 23 families from the study site. The most abundant species in all of the sites was Salvia Glutinosa cccIV = 0.52. The southern aspect depicted the lowest diversity, but had high species dominance. Allium carolinianum DC. in this site was the most important species (IV = 0.74). The most abundant species were medicinal plants (75%), followed by edible plants (25%). Aspect had a significant effect on the understory vegetation and different categories of plants with respect to their diversity, dominance, and evenness as predicted by the various diversity indices. This study provides essential insight in to the florisitic diversity and community structure of the fragile pine nut understory vegetation in South Waziristan, which was hitherto not available. It was concluded that the southern aspect of understudy dry temperate forests depicted lower diversity and density as compared with the northern aspect. But it was observed that the southern aspect more specifically had more density and diversity of medicinal plants. It is therefore the need of the hour that conservation of these species from grazing and unsustainable harvesting must be ensured to sustain the livelihood of the inhabitants.